2017
DOI: 10.15252/emmm.201606987
|View full text |Cite|
|
Sign up to set email alerts
|

Niacin ameliorates ulcerative colitis via prostaglandin D 2 ‐mediated D prostanoid receptor 1 activation

Abstract: Niacin, as an antidyslipidemic drug, elicits a strong flushing response by release of prostaglandin (PG) D2. However, whether niacin is beneficial for inflammatory bowel disease (IBD) remains unclear. Here, we observed niacin administration‐enhanced PGD2 production in colon tissues in dextran sulfate sodium (DSS)‐challenged mice, and protected mice against DSS or 2,4,6‐trinitrobenzene sulfonic acid (TNBS)‐induced colitis in D prostanoid receptor 1 (DP1)‐dependent manner. Specific ablation of DP1 receptor in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 60 publications
0
66
0
Order By: Relevance
“…Indeed, BW245C, a DP1 agonist, was shown to decrease colitis as well as the incidence of colitis-associated cancer in the DSS-azoxymethane model of colitis-associated cancer (7), whereas a DP1 antagonist worsened DSS-induced colitis (8). Moreover, 1 study showed that niacin administration to mice with DSS-and TNBS-induced colitis leads to an increase of PGD 2 production and subsequently to a decrease in colitis severity in a DP1-dependent manner (41). These studies point to a beneficial effect of DP1 in colitis that PGD 2 -G could be part of.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, BW245C, a DP1 agonist, was shown to decrease colitis as well as the incidence of colitis-associated cancer in the DSS-azoxymethane model of colitis-associated cancer (7), whereas a DP1 antagonist worsened DSS-induced colitis (8). Moreover, 1 study showed that niacin administration to mice with DSS-and TNBS-induced colitis leads to an increase of PGD 2 production and subsequently to a decrease in colitis severity in a DP1-dependent manner (41). These studies point to a beneficial effect of DP1 in colitis that PGD 2 -G could be part of.…”
Section: Discussionmentioning
confidence: 99%
“…This review aims to provide an overview of the roles of eicosanoids in physiological as well as pathogenic situations of tissue repair. As eicosanoids produced via the cyclooxygenase (COX) pathway (prostanoids) play particularly important roles in tissue repair, these mediators will be discussed in detail and with a focus on recent insights into their involvement in the repair of epithelial barriers …”
Section: Introductionmentioning
confidence: 99%
“…Newly deposited ECM then undergoes structural "remodeling" and the inflammatory response is terminated [e.g. by the action of lipoxin A 4 (LXA 4 )], thus resulting in "resolution" and the formation of new functional tissue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations